Copper/Iron cocatalyzed depolymerization of postconsumer polycarbonate: a one-pot strategy to synthesize aryl ethers - Moyilla, Nageswararao; Padhi, Ganeshdev; Kalsi, Deepti; Barsu, Nagaraju (ACS SUSTAINABLE CHEMISTRY & ENGINEERING, 2024)
Keywords: aryl ethers; copper/iron cocatalysis; depolymerization; polycarbonates; Value-added products

Ruthenium-catalyzed deconstruction of polyolefins: a strategy to up-cycle waste polyethylene to value-added alkene - Padhi, Ganeshdev; Khopade, Kishor V.; Moyilla, Nageswararao; Rangappa, Raghavendrakumar; Chikkali, Samir H.; Barsu, Nagaraju (Angewandte Chemie-International Edition, 2025)
Synthesis of value-added products from post-consumer waste polyolefins is fascinating as well as challenging. Here we report ruthenium-catalyzed up-cycling of the polyethylene to long-chain alkene derivatives. The developed methodology mainly involves two steps i.e., dehydrogenation of polyethylene through hydrogen atom transfer and its metathesis using the HG-II catalyst. The dehydrogenation of polyethylene using ruthenium catalysis derived up to 3.38 %, of double bonds; with 90 % of the recovered polyolefin material. The obtained unsaturated polyethylene was subjected to cross-metathesis with ethylene using HG-II catalytic system. This resulted in the synthesis of predominantly dodecene (C12) derivatives, with 58 % selectivity, along with other derivatives of varying chain lengths. The overall reaction produced terminal and internal olefins in the ratio 1:0.8 respectively. The dehydrogenation of polyethylene and its deconstruction was confirmed by NMR spectroscopy, Gel Permeation Chromatography (GPC) and Differential Scanning Calorimetry (DSC). The origin of C12 selectivity has been demonstrated by control experiments. The scope of the methodology was extended to post-consumer waste polyethylene which gave high conversion to value-added dodecene derivatives as a major product.
Keywords: Deconstruction; Homogeneous catalysis; ruthenium; Upcycling; Waste plastic

Sustainable base-mediated chemical upcycling of poly (propylene carbonate) to β-hydroxy sulfides and oxides - Moyilla, Nageswararao; Padhi, Ganeshdev; Barsu, Nagaraju (Green Chemistry, 2025)
We present a cesium carbonate-mediated method to upcycle poly(propylene carbonate) (PPC) waste into beta-hydroxy sulfides, selenides, and phenoxides via selective thermal depolymerization. The process tolerates diverse nucleophiles, including those from multilayer plastics. Mechanistic studies support a cesium aryl thiolate-driven nucleophilic degradation. The beta-hydroxy products are easily functionalized, and the base is recyclable, offering a sustainable route for PPC valorization.